Biomass residues improve soil chemical and biological properties reestablishing native species in an exposed subsoil in Brazilian Cerrado - Soto Boni, Thaís [UNESP]; Pujol Pereira, Engil Isadora; Avelino Santos, Adriana [UNESP]; Rodrigues Cassiolato, Ana Maria [UNESP]; Maltoni, Kátia Luciene [UNESP] (Public Library of Science (PLoS), 2022)
Revegetation of exposed sub-soil, while a desirable strategy in the recovery processes, often fails due to extreme soil chemical properties, such as low organic matter and pH levels inhospitable to biological activities such as nutrients cycling and plant establishment. This is the case for approximately 800 ha of the Cerrado biome in Brazil, where erecting the embankment of a hydroelectric dam in the 1960's stripped vegetation, soil, and subsoil layers thereby distorting the soil properties. This work evaluates the effectiveness of restoration management (RM) treatments, to restore the soil quality, including biological activity and chemical attributes. In a factorial scheme, RM treatments include the addition of organic residue from aquatic macrophytes (AM) at 3 rates (0, 16 and 32 t ha-1), combined with ash from sugar cane bagasse of agroindustrial origin (BA) at 4 rates (0, 15, 30 and 45 t ha-1). RM samples contrasted samples collected from undisturbed Cerrado (CER) as well as a degraded area without intervention (DAWI). The mechanized RM plots received amendments and reforestation of 10 Cerrado native tree species. After 5 years, vegetation covered up to 60% of the surface in RM treatments receiving AM32 + BA45. AM and BA residues promoted height increases in the introduced plants. All RM treatments promoted lower levels of Al3+ than DAWI and CER. The combination of AM32 over the rates of incorporated ash increased soil pH and K values similarly to CER. Microbial-related variables, such as microbial biomass-C was the largest in CER, followed by the RM treatments, and the lowest in DAWI. The microbial quotient was no different between CER and RM treatments. The addition of residues such as AM and BA increased the vegetation covered, improved chemical and microbiological indicators. Thus, the residues used aided the recovery process of intensely degraded soils in the Cerrado area.